Effects of drain quiescent voltage on the ageing of AlGaN/GaN HEMT devices in pulsed RF mode. (September 2016) - Divay, A.; Duperrier, C.; Temcamani, F.; Latry, O.
Abstract: The reliability of RF AlGaN/GaN HEMT devices on SiC substrate is investigated here in pulsed RF condition at nominal and maximum rating drain quiescent bias. During these 3500 hour tests, high voltage especially during the RF pulse leads to a progressive decrease in g m and I DSS while trap concentration increases. These evolutions may be attributed to trap generation by hot carrier injection and highlight the importance of drain quiescent voltage as an important acceleration factor for this technology's reliability in pulsed RF conditions. Highlights: Athermal DC Transient Spectroscopy was performed before and after ageing in order to characterize the trapping effect evolution. Ageing in operational radar conditions of high power amplifier AlGaN/GaN HEMT transistors (Pulsed RF-HTOL). Extraction of traps at Ea = Ev + 0.8 eV, Ea = Ev − 0, 74 eV and Ea = Ev − 0, 65 eV.